The IDEA OF CONSTRUCTIVE FEMINISM IN NAGUIB MAHFOUZ’S THE ANSWER IS NO - Toto Indra Wijaya; Laila Nabilahtuzzahro Ibrahim; Cahyaningsih Pujimahanani; Rommel Utungga Pasopati (KOLONI, 2023)
Constructive feminism claims that gender is socially constructed by the domination of men. Being constructive then also indicated that women could define their own meanings by themselves. The Answer is No is a short story written by Naguib Mahfouz. It explores dilemma of a female teacher who was assaulted by a trusted tutor at fourteen years old and now faces the perpetrator as her school's new headmaster. The woman refuses to yield before the man and chooses to maintain her dignity and self-respect. Through qualitative method, this paper underlines constructive feminism in which the woman could choose her own story for her future. Despite all her bad past memories, she could keep going on by saying no as her main answer. In conclusion, constructive feminism is crucial in the daily life of women since it could criticize matter of domination of men alongside with any possibility for woman to move forward. Keywords: Constructive Feminism, Gender, Naguib Mahfouz, The Answer is No